Product wear-resistant and corrosion-resistant remanufacturing process method based on laser deposition
Through functional gradient coating design and laser deposition technology, the problems of weak stress concentration and bonding force of the coating in the existing process are solved, and the coating is high wear resistance, corrosion resistance and long life are achieved, and the service life of the equipment is extended.
Patent Information
- Application Number
- CN202411947100.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
The existing product wear-resistant and corrosion-resistant remanufacturing processes based on laser deposition have problems such as peeling caused by concentrated coating stress, weak bonding force, different thermal expansion coefficients, and imperfect surface treatment, which affects its long-term stability and durability.
Through functional gradient coating design, combined with laser cladding and ion deposition technology, the inner layer toughness and outer layer hardness are formed to form an organic combination of inner layer toughness, enhance the adhesion and wear resistance of the coating, and eliminate residual stress through low-temperature annealing and mirror polishing treatment to improve finish and durability.
It achieves excellent stability and long life of the coating, maintains mechanical stability and durability in high wear and high corrosion environments, and extends the service life of the equipment.
Smart Images

Figure CN119710692A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a wear-resistant and corrosion-resistant remanufacturing process method for products based on laser deposition. Background Art
[0002] With the long-term service of industrial equipment, especially key components working in high wear and corrosion environments, such as coal mining machinery, oil drilling equipment, etc., the surface of the equipment is susceptible to severe wear and corrosion, resulting in a significant decline in its performance and life. In order to extend the service life of equipment and reduce maintenance costs, remanufacturing technology has become an effective way to solve this problem. Among them, the wear-resistant and corrosion-resistant coating remanufacturing technology based on laser deposition has been widely used because it can form a dense and high-strength coating on the surface of the equipment. Through laser cladding and deposition of ceramic materials, the remanufacturing process can effectively improve the wear resistance and corrosion resistance of the equipment, enabling it to operate stably for a long time under harsh working conditions.
[0003] The current wear-resistant and corrosion-resistant remanufacturing process of products based on laser deposition usually uses laser cladding technology to deposit a layer of wear-resistant alloy coating on the surface of the equipment. The alloy powder is melted by a high-energy laser beam to form a metallurgical bond between the coating and the substrate, thereby enhancing the adhesion and wear resistance of the coating.
[0004] However, the existing remanufacturing process still has certain shortcomings in practical applications. First, the single-layer laser cladding coating is prone to stress concentration problems when dealing with complex working conditions, causing cracking or peeling of the coating, affecting its long-term stability; second, the existing ceramic deposition coating often has weak bonding with the substrate and is prone to peeling due to differences in thermal expansion coefficients; in addition, the surface treatment process of the coating is not perfect, the residual stress has not been effectively eliminated, and the smoothness and durability of the coating have not yet reached an ideal level. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a wear-resistant and corrosion-resistant remanufacturing process method for products based on laser deposition. The present invention realizes the organic combination of inner layer toughness and outer layer hardness through functional gradient coating design, thereby improving the wear resistance and corrosion resistance of the coating. The metallurgical bonding of the coating enhances the adhesion and avoids the problems of cracking and peeling of the coating. At the same time, low-temperature annealing treatment and mirror polishing effectively eliminate residual stress and improve the smoothness and durability of the coating, so that it has excellent stability and life in high wear and high corrosion environments.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A wear-resistant and corrosion-resistant remanufacturing process method for products based on laser deposition, comprising the following steps:
[0007] Surface pretreatment: pre-treat the substrate surface of the product to remove the surface oxide layer, oil stains and other impurities to improve the adhesion of the coating;
[0008] Preparation of laser cladding coating: On the pretreated substrate surface, a first layer of wear-resistant coating is deposited by laser cladding process, wherein the wear-resistant coating is Fe-based or Co-based multi-component alloy powder;
[0009] Preparation of ion deposition coating: forming a second layer of corrosion-resistant coating on the first layer of coating by ion deposition process, wherein the corrosion-resistant coating is a ceramic material;
[0010] Surface post-treatment: Heat treatment and surface finishing of the coating to reduce residual stress and ensure the surface smoothness and durability of the coating.
[0011] Preferably, the surface pretreatment comprises the following steps:
[0012] Sand blasting: Use corundum sand or silicon carbide particles to sandblast the substrate surface to increase the surface roughness;
[0013] Chemical cleaning: Immerse the substrate surface after sandblasting in a dilute sulfuric acid or hydrochloric acid solution for chemical cleaning to remove surface oxides and impurities;
[0014] Surface Roughening: Depending on the substrate material, mechanical grinding or chemical etching is used to further roughen the surface to enhance the adhesion of the coating.
[0015] Preferably, the laser cladding coating preparation comprises the following steps:
[0016] Select Fe-based or Co-based multi-component alloy powder, the particle size range of the alloy powder is 20 to 100 microns;
[0017] The laser cladding process is adopted, the laser power is set at 2-4kW, and the cladding scanning speed is controlled at 5-10mm / s;
[0018] The cladding thickness is controlled at 0.5 to 2.0 mm, and multi-layer uniform cladding is achieved through a cross-scanning path to ensure metallurgical bonding between the coating and the substrate.
[0019] Preferably, Ti, V and W strengthening elements are added to the laser cladding coating material to form carbide, nitride or boride particles to improve the hardness and wear resistance of the coating, and the coating hardness reaches above HV600.
[0020] Preferably, the ion deposition coating preparation comprises the following steps:
[0021] On the first layer of laser cladding coating, a pulsed arc ion source technology is used to deposit silicon nitride (Si3N4), aluminum oxide (Al2O3) or titanium nitride (TiN) ceramic materials;
[0022] Adjust the deposition current to 50-200A / cm 2 , ensuring the uniformity and density of the deposited layer;
[0023] The deposition thickness is controlled to be 10 to 100 microns, and the coating thickness is adjusted according to demand to ensure the corrosion resistance of the coating.
[0024] Preferably, the particle size of the ceramic material powder is controlled to be 1 to 10 microns, and the deposition atmosphere is 10 -4 ~10 -6 Pa vacuum environment, and introduce nitrogen or oxygen as the reaction gas.
[0025] Preferably, the surface post-treatment comprises the following steps:
[0026] The coating is subjected to low-temperature annealing treatment at 200-400°C for 2-4 hours to eliminate residual stress inside and outside the coating;
[0027] Use mechanical polishing or ultra-precision polishing technology to fine-process the coating surface so that the surface roughness reaches the mirror state of Ra0.2~0.4;
[0028] Cooling curve control, gradually reducing the coating temperature to prevent stress concentration caused by differences in thermal expansion coefficients.
[0029] Preferably, the multi-layer coating structure is a double-layer or multi-layer composite coating, the first layer is a wear-resistant laser cladding layer, the second layer is a corrosion-resistant ceramic deposition layer, and the layers are metallurgically bonded to achieve stress-free transition.
[0030] Preferably, the thickness and material composition of each layer in the multilayer coating can be adjusted according to different working conditions, specifically including a functional gradient coating that gradually transitions from the inside to the outside, wherein the first layer contains a metal-ceramic composite material and the second layer is a pure ceramic material.
[0031] Preferably, the hardness of the functional gradient coating is designed to gradually increase from the inside to the outside, wherein the hardness of the inner layer is HV600, and the hardness of the outer ceramic coating can reach above HV1000, meeting the requirements of high wear and high corrosion service environments.
[0032] The present invention provides a product wear-resistant and corrosion-resistant remanufacturing process method based on laser deposition. It has the following beneficial effects:
[0033] 1. The present invention designs a functional gradient coating. The inner metal-ceramic composite material provides excellent toughness and impact resistance, and the outer ceramic material such as titanium nitride or aluminum oxide greatly improves the wear resistance and corrosion resistance, thereby realizing a structure in which the hardness of the coating gradually increases from the inside to the outside, effectively improving the wear resistance, corrosion resistance and long-term stability of the coating.
[0034] 2. The present invention ensures strong adhesion between the inner layer and the base material through metallurgical bonding of the coating, avoiding the risk of coating peeling and cracking. At the same time, the gradient design reduces coating failure caused by stress concentration, enabling it to have excellent mechanical stability and durability in high temperature, high wear and corrosion environments.
[0035] 3. The present invention effectively eliminates the residual stress of the coating through low-temperature annealing treatment and gradual temperature reduction control. The coating surface achieves mirror finish after polishing, reduces the friction coefficient, improves the durability of the coating in high-stress and high-wear environments, and extends the service life of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Please see attached Figure 1 The embodiment of the present invention provides a product wear-resistant and corrosion-resistant remanufacturing process method based on laser deposition, comprising the following steps:
[0039] Surface pretreatment: Pre-treat the substrate surface of the product to remove the surface oxide layer, oil stains and other impurities to improve the adhesion of the coating. The surface pretreatment step combines sandblasting and chemical cleaning to not only effectively remove impurities on the substrate surface, but also improve the bonding strength between the coating and the substrate, avoiding the problem of poor coating adhesion caused by unclean surface or insufficient roughness;
[0040] Laser cladding coating preparation: On the pretreated substrate surface, the first layer of wear-resistant coating is deposited by laser cladding process. The wear-resistant coating is Fe-based or Co-based multi-component alloy powder. The laser cladding process forms a strong metallurgical bond with the substrate material by precisely controlling the process parameters. The wear resistance of the coating is significantly improved by adding strengthening elements, which prolongs the service life of the equipment and ensures the thickness uniformity and bonding strength of the coating.
[0041] Preparation of ion deposition coating: On the first coating layer, a second corrosion-resistant coating is formed by an ion deposition process. The corrosion-resistant coating is a ceramic material. The ceramic coating forms a dense and uniform protective layer by ion deposition, which can effectively prevent the corrosive medium from further eroding the cladding layer and the substrate. It is particularly suitable for applications in highly corrosive environments. The ceramic coating deposited by the ion deposition process has extremely high density and uniformity, which enhances the corrosion resistance of the product. Especially in extremely corrosive environments, the coating can permanently protect the substrate material and avoid premature failure of the equipment due to corrosion;
[0042] Surface post-treatment: Heat treatment and surface finishing of the coating to reduce residual stress and ensure the surface smoothness and durability of the coating. Through the combination of low-temperature annealing and mechanical polishing, the stress inside the coating is effectively released, avoiding the risk of coating cracking. At the same time, the surface smoothness and durability are also significantly improved, further improving the comprehensive performance of the coating and extending the service life of the equipment.
[0043] Please see attached Figure 1 In a preferred embodiment of the present invention, the surface pretreatment comprises the following steps:
[0044] Sandblasting: Use corundum sand or silicon carbide particles to sandblast the substrate surface to increase the surface roughness. In specific implementation, sandblasting uses corundum sand or silicon carbide particles as sandblasting media. The main component of corundum sand is aluminum oxide, which has high hardness and good wear resistance, while silicon carbide has higher hardness and chemical stability. It is particularly suitable for treating the surface of materials with thick surface oxide layers or hard substrates. After sandblasting, the substrate surface not only becomes cleaner, but also produces a uniform rough surface. This microscopic concave-convex structure provides more contact area for subsequent coatings and improves the mechanical adhesion of the coating. Sandblasting can effectively remove dirt and oxide layers on the substrate surface through high-speed particle impact, and at the same time create a uniform roughness for the substrate surface, thereby improving the adhesion performance of subsequent coatings and ensuring that the coating is not easy to fall off during use;
[0045] Chemical cleaning: The surface of the substrate after sandblasting is immersed in a dilute sulfuric acid or hydrochloric acid solution for chemical cleaning to remove surface oxides and impurities. In specific implementation, the substrate after sandblasting is first immersed in a dilute sulfuric acid or hydrochloric acid solution, and after the pickling is completed, the surface is immediately cleaned with deionized water to ensure that the acid and surface impurities are completely removed to prevent the acid residue from causing secondary corrosion to the substrate. Through the pickling process, the tiny particles and oxides remaining on the substrate surface after sandblasting can be completely removed, and the surface cleanliness can be further improved to ensure that the coating can achieve the best adhesion effect with the substrate surface in the subsequent process;
[0046] Surface roughening: Depending on the substrate material, mechanical grinding or chemical etching is used to further roughen the surface to enhance the adhesion of the coating. Mechanical grinding: The substrate surface is polished using a high-speed rotating grinding tool (such as a grinding wheel or abrasive belt) to form a more uniform microscopic concave-convex structure, further increasing the surface roughness. Chemical etching: For substrate materials that are difficult to mechanically grind (such as complex shapes or brittle materials), it is more appropriate to use a chemical etching process. Chemical etching is to immerse the substrate material in a specific acidic or alkaline solution to cause local corrosion of the surface material, thereby forming a microscopic rough structure. The surface roughening process greatly improves the bonding strength between the coating and the substrate by further increasing the microscopic roughness of the surface. It is especially suitable for product components working under high stress and complex working conditions, ensuring that the coating can still maintain excellent adhesion and durability in harsh environments.
[0047] Please see attached Figure 1 In a preferred embodiment of the present invention, the laser cladding coating preparation comprises the following steps:
[0048] Fe-based or Co-based multi-component alloy powder is selected, and the particle size of the alloy powder ranges from 20 to 100 microns. Fe-based alloy powder: mainly composed of iron (Fe) as the matrix element, and chromium (Cr), nickel (Ni), molybdenum (Mo) and other elements are often added. These alloy elements can enhance the wear resistance, corrosion resistance and high-temperature oxidation resistance of the coating. Chromium can form a dense oxide film on the surface to improve the oxidation resistance and corrosion resistance of the coating; nickel enhances the high-temperature stability and corrosion resistance of the coating; and molybdenum can improve the corrosion resistance, especially suitable for acidic corrosion environments. Co-based alloy powder: Alloys based on cobalt (Co) have excellent high-temperature strength, wear resistance and corrosion resistance, and are especially suitable for high-temperature and high-wear conditions. Co-based alloys usually contain strengthening phases such as tungsten carbide (WC), which can improve the hardness and wear resistance of the alloy coating. By selecting Fe-based or Co-based multi-component alloy powders of appropriate particle size, a dense and uniform coating structure can be obtained during the cladding process, which improves the wear resistance, corrosion resistance and high-temperature performance of the coating, while reducing pores and cracks in the coating;
[0049] The laser cladding process is adopted, the laser power is set at 2-4kW, and the cladding scanning speed is controlled at 5-10mm / s. The laser cladding process ensures that the alloy powder can be evenly distributed during the cladding process by precisely controlling the laser power and scanning speed, and forms a strong metallurgical bond with the substrate material, thereby improving the strength and durability of the coating and avoiding overheating or dilution of the substrate.
[0050] The cladding thickness is controlled at 0.5-2.0 mm, and multi-layer uniform cladding is achieved through a cross-scanning path to ensure that the coating forms a metallurgical bond with the substrate. By controlling the thickness of the cladding layer and adopting a cross-scanning path design, not only can a uniform and dense coating structure be obtained, but the wear resistance and corrosion resistance of the coating can also be greatly improved, the defects and stress concentration problems in the overlap area can be reduced, and the service life of the coating can be extended.
[0051] Please see attached Figure 1 In a preferred embodiment of the present invention, Ti, V and W strengthening elements are added to the laser cladding coating material to form carbide, nitride or boride particles to improve the hardness and wear resistance of the coating, and the coating hardness reaches above HV600;
[0052] Among them, Ti (titanium): During the cladding process, titanium can react with carbon or nitrogen to form titanium carbide (TiC) or titanium nitride (TiN) particles. These hard phase particles have extremely high hardness and can improve the wear resistance and oxidation resistance of the coating. In addition, TiC particles also have a low density and can enhance the hardness of the coating without significantly increasing the weight of the coating;
[0053] V (vanadium): Vanadium reacts with carbon or nitrogen to form vanadium carbide (VC) or vanadium nitride (VN). Vanadium carbide particles have extremely high hardness (HV2700 or above), and can form a strengthening phase in the coating, effectively enhancing the wear resistance of the coating, while increasing the toughness of the coating to prevent brittle failure. In addition, vanadium carbide and vanadium nitride also significantly improve the oxidation resistance and corrosion resistance in high temperature environments.
[0054] W (tungsten): Tungsten can be combined with carbon or boron to form tungsten carbide (WC) or tungsten boride (WB) during the cladding process. Tungsten carbide particles have extremely high hardness (HV2000 or above) and are often used to improve the wear resistance of the coating. WC particles are evenly dispersed in the coating, which can improve the wear resistance of the coating, especially under strong abrasive wear conditions.
[0055] By adding strengthening elements such as Ti, V, and W to the cladding material, high-hardness carbide, nitride, and boride particles can be generated to form a uniformly distributed hard phase, thereby improving the hardness and wear resistance of the coating;
[0056] By generating carbide, nitride and boride particles in the laser cladding coating, the uniform distribution of hard phase particles enables the coating to exhibit excellent wear resistance, corrosion resistance and high temperature resistance when subjected to wear, corrosion and high temperature;
[0057] The hard phase particles generated by the strengthening elements can increase the hardness of the coating to above HV600, while ensuring that the coating still has excellent mechanical properties in high wear, high impact and high temperature environments. This coating design not only has extremely high wear resistance, but also maintains the toughness and impact resistance of the coating.
[0058] Please see attached Figure 1 In a preferred embodiment of the present invention, the ion deposition coating preparation comprises the following steps:
[0059] On the first layer of laser cladding coating, pulse arc ion source technology is used to deposit silicon nitride (Si3N4), aluminum oxide (Al2O3) or titanium nitride (Tin) ceramic materials, among which silicon nitride: Silicon nitride is an excellent ceramic material with extremely high strength, hardness and oxidation resistance, especially suitable for high temperature and corrosion-resistant environment. Its thermal shock resistance and high temperature strength are especially suitable for equipment that needs to withstand high temperature and wear for a long time.
[0060] Alumina: Alumina is a common ceramic material with excellent hardness and wear resistance. Its high temperature resistance is also very outstanding, making it suitable for high-temperature components in industrial equipment. Alumina coating can not only improve wear resistance, but also has good electrical insulation.
[0061] Titanium nitride: Titanium nitride has extremely strong hardness and wear resistance. It is usually used in cutting tools and molds to enhance their service life. The corrosion resistance of titanium nitride coating is also very good, especially in oxidizing environments, and can effectively resist the erosion of corrosive media;
[0062] Adjust the deposition current to 50-200A / cm 2 To ensure the uniformity and density of the deposited layer, the deposition current is controlled at 50-200A / cm 2 , which can achieve uniform deposition and high density of ceramic coating, greatly improve the wear resistance and corrosion resistance of the coating, and at the same time prevent the occurrence of surface defects of the coating, ensuring the overall performance of the coating;
[0063] The deposition thickness is controlled to be 10 to 100 microns. The coating thickness is adjusted according to demand to ensure the corrosion resistance of the coating. By controlling the thickness of the ceramic coating between 10 and 100 microns, the coating performance can be optimized in different working environments. Thick coatings can provide stronger corrosion resistance and wear resistance, while thin coatings have better precision and processing efficiency. This thickness control ensures the overall quality and durability of the coating, while avoiding the peeling problem caused by excessively thick coatings.
[0064] Please see attached Figure 1 In a preferred embodiment of the present invention, the particle size of the ceramic material powder is controlled to be 1 to 10 microns, and the deposition atmosphere is 10 -4 ~10 -6 Pa vacuum environment, and introduce nitrogen or oxygen as the reaction gas, the particle size range of 1 to 10 microns can ensure that the powder is quickly ionized under the pulse arc ion source technology and can be evenly distributed in the coating, thereby improving the surface flatness of the coating, enhancing the wear resistance and corrosion resistance of the coating, and adapting to different application requirements;
[0065] By controlling the deposition atmosphere to 10 -4 ~10 -6 The vacuum environment of Pa can reduce impurities and pores in the coating, improve the purity and density of the coating, enhance its corrosion resistance and wear resistance, and ensure the stability and service life of the coating in a high-corrosion and high-wear environment;
[0066] By introducing nitrogen or oxygen as reaction gas, the formation of nitride or oxide coating can be promoted, thereby significantly improving the hardness, wear resistance and corrosion resistance of the coating. The anti-oxidation performance of the coating is also enhanced, making it suitable for use under extreme working conditions such as high temperature and high corrosion.
[0067] Please see attached Figure 1 In a preferred embodiment of the present invention, the surface post-treatment comprises the following steps:
[0068] The coating is subjected to low-temperature annealing treatment at 200-400°C for 2-4 hours to eliminate residual stress inside and outside the coating. The low-temperature annealing treatment at 200-400°C can eliminate the residual stress inside the coating, prevent the coating from cracking or peeling during service, and improve the mechanical stability and service life of the coating. This time can effectively release the stress inside the coating;
[0069] Use mechanical polishing or ultra-precision polishing technology to fine-process the coating surface so that the surface roughness reaches the mirror state of Ra0.2-0.4. Mechanical polishing and ultra-precision polishing can improve the surface finish of the coating, reduce the friction coefficient, and make the coating surface reach the mirror state of Ra0.2-0.4, thereby enhancing the wear resistance and corrosion resistance, and extending the service life of the equipment;
[0070] Cooling curve control gradually reduces the coating temperature to prevent stress concentration caused by differences in thermal expansion coefficients. Cooling curve control means that after annealing or processing of the coating, the temperature of the coating and the substrate material is gradually balanced by lowering the temperature in stages to avoid the accumulation of thermal stress in the coating. By gradually reducing the coating temperature and controlling the cooling curve, stress concentration caused by differences in thermal expansion coefficients between the coating and the substrate can be avoided, cracking or peeling of the coating during use can be prevented, and the long-term stability of the coating can be ensured.
[0071] Please see attached Figure 1 In a preferred embodiment of the present invention, the multilayer coating structure is a double-layer or multi-layer composite coating, the first layer is a wear-resistant laser cladding layer, the second layer is a corrosion-resistant ceramic deposition layer, and the layers are metallurgically bonded to achieve stress-free transition. The first layer of the double-layer coating is a laser cladding layer, which uses Fe-based or Co-based multi-component alloy powder to improve the wear resistance of the substrate surface; the second layer is a ceramic layer deposited by pulse arc ion source technology, which is mainly used to improve the corrosion resistance of the coating. This double-layer coating design is particularly suitable for applications such as coal mining equipment and oil drilling equipment that need to withstand strong wear and corrosion. The wear-resistant layer prepared by the laser cladding process forms a metallurgical bond with the substrate material, ensuring the high adhesion and durability of the coating. At the same time, the addition of hard phase particles significantly improves the hardness of the coating, enabling it to work stably for a long time in a high-wear environment. The ceramic deposition layer is deposited on the cladding layer by pulse arc ion source technology, which not only provides high hardness and wear resistance, but also has excellent corrosion resistance, and is suitable for various harsh corrosive working conditions. The denseness of the coating further ensures its long-term stability.
[0072] Please see attached Figure 1In a preferred embodiment of the present invention, the thickness and material composition of each layer in the multilayer coating can be adjusted according to different working conditions, specifically including a functional gradient coating that gradually transitions from the inside to the outside, wherein the first layer contains a metal-ceramic composite material and the second layer is a pure ceramic material. Through the gradual transition of the functional gradient coating design, the coating can exhibit excellent comprehensive performance in different working environments. The inner layer provides good toughness and impact resistance, while the outer layer improves wear resistance and corrosion resistance, thereby extending the service life of the equipment. The inner layer of the metal-ceramic composite material not only maintains the toughness and impact resistance of the coating through the synergistic effect of the metal matrix and the ceramic particles, but also improves the hardness and wear resistance of the coating, thereby ensuring that the coating can still work stably under high wear and high stress environments. The outer layer of the pure ceramic material provides the functional gradient coating with strong wear resistance and corrosion resistance, especially under high temperature and high corrosion conditions. The pure ceramic material can effectively prevent wear and corrosion of the coating, thereby extending the service life of the equipment and reducing maintenance costs.
[0073] Please see attached Figure 1 In a preferred embodiment of the present invention, the hardness of the functional gradient coating is designed to gradually increase from the inside to the outside, wherein the hardness of the inner layer is HV600, and the hardness of the outer ceramic coating can reach HV1000 or more, meeting the service environment of high wear and high corrosion. By gradually transitioning the hardness from HV600 of the inner layer to HV1000 or more of the outer layer, the coating can not only withstand high-intensity mechanical impact, but also effectively resist high friction wear and erosion of corrosive media, ensuring that the equipment has a longer service life in complex working conditions;
[0074] Reasonable design of the hardness of the inner layer enables the coating to withstand mechanical impact and stress concentration, which can effectively improve the stability and durability of the coating and ensure that it does not crack or peel off due to stress;
[0075] The high hardness design of the outer ceramic material makes the coating have excellent wear resistance and corrosion resistance, which can effectively prevent the surface of the equipment from being scratched, worn or corroded by corrosive media, thereby greatly extending the service life of the equipment;
[0076] Through the functional gradient coating design with gradually increasing hardness, the coating can effectively cope with the working conditions of high wear and high corrosion, and avoid the failure of the coating due to stress concentration, thereby extending the service life of the coating and equipment, improving work efficiency and reducing maintenance costs.
[0077] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments.
[0078] Example 1: Remanufacturing process for wear-resistant and corrosion-resistant coating of hydraulic support column for coal mine equipment
[0079] In this embodiment, the functional gradient coating is designed for hydraulic support columns of coal mine equipment, and the working environment of the equipment has the characteristics of high wear and high corrosion. The surface of the support column is remanufactured by a process method combining laser cladding and ceramic deposition.
[0080] Inner layer material: Fe-based multi-component alloy powder is used, the inner layer thickness is 1.5mm, the hardness is HV600, and titanium carbide (TiC) particles are added to the inner layer to enhance wear resistance while maintaining good toughness, which is suitable for bearing the high mechanical stress and impact load of the hydraulic support column during operation.
[0081] Outer layer material: The outer layer is a titanium nitride (T i N) ceramic coating with a thickness of 50 microns and a hardness of HV1500. This layer has extremely strong wear resistance and corrosion resistance. It can effectively resist wear in the high wear environment of underground coal mines and prevent corrosive media from eroding the equipment surface.
[0082] Example 2: Remanufacturing process of high temperature wear-resistant coating for oil drilling equipment drill pipe
[0083] In this embodiment, the functional gradient coating is designed and applied to the surface of the drill pipe of the oil drilling equipment. The equipment works in a high temperature and high corrosion environment, and the coating is required to have extremely high wear resistance and corrosion resistance.
[0084] Inner layer material: Co-based multi-component alloy powder is used, the inner layer thickness is 2.0mm, the hardness is HV700, tungsten carbide (WC) particles are added to the Co-based alloy to form a metal-ceramic composite layer, which provides extremely high wear resistance and impact resistance, and is suitable for high temperature and high pressure environments in oil drilling.
[0085] Outer material: The outer layer is a silicon nitride coating with a thickness of 75 microns and a hardness of HV1800. This layer has excellent wear resistance and high-temperature oxidation resistance. It can work for a long time in a high temperature, wear and corrosion environment to prevent oxidation and mechanical damage to the drill pipe surface.
[0086] Example 3: Remanufacturing process of corrosion-resistant coating for marine engineering equipment blades
[0087] In this embodiment, the functional gradient coating is applied to the surface of the turbine blades of marine engineering equipment. The equipment is exposed to the seawater environment for a long time, and the coating is required to have extremely strong corrosion resistance and moderate wear resistance.
[0088] Inner layer material: The inner layer is made of Fe-based multi-component alloy powder with a thickness of 1.0mm and a hardness of HV600. Titanium carbide (T i C) and molybdenum (Mo) particles are added to the alloy to enhance corrosion resistance and wear resistance, enabling it to resist abrasive wear in the marine environment and prevent pitting and stress corrosion on the blade surface.
[0089] Outer material: The outer layer is an alumina ceramic coating with a thickness of 50 microns and a hardness of HV1200. The alumina coating can provide extremely strong corrosion resistance and is particularly suitable for long-term use in seawater and salt spray environments to prevent the surface of the equipment from being corroded by corrosive media.
[0090] Example 4: Remanufacturing process for wear-resistant coating on the surface of wind turbine bearing
[0091] In this embodiment, the functional gradient coating is applied to the surface of the wind turbine bearing. The equipment works under high-speed rotation and high load, and the coating is required to have high wear resistance and fatigue resistance.
[0092] Inner layer material: Fe-based alloy powder with a thickness of 1.2mm and a hardness of HV650. Tungsten carbide (WC) particles are added to the alloy to enhance the wear resistance of the inner layer, ensure that friction stress can be effectively dispersed under high load, and prevent coating wear and fatigue failure.
[0093] Outer layer material: The outer layer is a titanium nitride (T iN) coating with a thickness of 60 microns and a hardness of HV1500. The extremely high hardness of the T iN coating enables it to resist friction damage to the bearing during high-speed rotation while providing anti-oxidation protection.
[0094] Comparative experiment 1: wear resistance experiment
[0095] Experimental purpose: To evaluate the wear resistance of the functional gradient coating of the present invention in a high wear environment.
[0096] Experimental setup:
[0097] Experimental group: functional gradient coating (inner layer is Fe-based + TiC, outer layer is titanium nitride TiN), hardness gradient design from HV600 to HV1000.
[0098] Control group: single-layer laser cladding coating (Fe-based + TiC), with a hardness of HV600.
[0099] Experimental equipment:
[0100] The dry sand rubber wheel wear tester was used according to ASTM G65 standard.
[0101] Experimental steps:
[0102] Sample preparation: Prepare test samples of functional gradient coating and single-layer laser cladding coating. The sample specifications are cylindrical, with a diameter of 10 mm and a height of 30 mm.
[0103] Initial mass measurement: Use a precision electronic balance to record the initial mass of each sample to an accuracy of 0.001 g.
[0104] Wear test: The samples were fixed in the testing machine and operated under the same load (100N) and rotation speed (200rpm). Each sample was subjected to wear test for 10 minutes. The abrasive was medium-grained quartz sand.
[0105] Post-wear mass measurement: After the test, the samples are cleaned and their mass loss is measured.
[0106] Wear volume calculation: According to the mass loss, calculate the wear volume (mm 3 ).
[0107] Surface observation: Scanning electron microscopy (SEM) was used to observe the surface morphology after wear and record cracks and wear marks.
[0108] The comparative experimental data are shown in Table 1:
[0109] Table 1 Wear resistance test results
[0110]
[0111] From the data in Table 1, we can get:
[0112] This comparative experiment proves that the functional gradient coating of the present invention has significantly better wear resistance than the existing single-layer laser cladding coating in a high wear environment. This is mainly due to the functional gradient design of the present invention in which the hardness gradually increases from the inside to the outside. The high-hardness ceramic material of the outer layer provides excellent wear resistance, while the metal-ceramic composite material of the inner layer provides good impact resistance and stress dispersion.
[0113] Comparative experiment 2: Corrosion resistance experiment
[0114] Experimental purpose: To evaluate the corrosion resistance of the functional gradient coating of the present invention in a corrosive environment.
[0115] Experimental setup:
[0116] Experimental group: functional gradient coating (inner layer is Fe-based + TiC, outer layer is alumina ceramic coating), high-density ceramic layer provides excellent corrosion protection.
[0117] Control group 1: single-layer laser cladding coating (Fe-based + TiC) without ceramic layer protection.
[0118] Control group 2: traditional electroplated chrome coating, as a conventional anti-corrosion treatment technology.
[0119] Experimental equipment:
[0120] Use a salt spray test machine (salt spray corrosion chamber) to conduct salt spray corrosion tests in accordance with ASTM B117 standards to simulate the corrosion of the equipment surface in a salt spray environment.
[0121] Experimental steps:
[0122] Sample preparation: functional gradient coating samples, single-layer laser cladding coating samples and electroplated chrome coating samples were prepared. The sample specifications were standard square metal test pieces (20 mm × 20 mm × 5 mm).
[0123] Initial mass measurement: The initial mass of each sample was recorded to the nearest 0.001 g using a precision balance.
[0124] Salt spray corrosion test: Place the sample in a salt spray tester. The salt spray solution is 5% sodium chloride solution. The test time is 72 hours and the temperature is maintained at 35°C.
[0125] Post-corrosion mass measurement: After the test, clean the sample surface to remove corrosion products, record the post-corrosion mass of each sample, and calculate the mass loss.
[0126] Surface observation: Optical microscope and scanning electron microscope (SEM) were used to observe the surface morphology of the coating after corrosion and analyze the corrosion pits, oxides and pitting.
[0127] The comparative experimental data are shown in Table 2:
[0128] Table 2 Corrosion resistance test results
[0129]
[0130]
[0131] From the data in Table 2, we can get:
[0132] The functional gradient coating of the present invention has significant advantages in corrosion resistance. Due to the use of an outer layer of ceramic material, the functional gradient coating exhibits extremely high corrosion resistance in a salt spray corrosion environment, and the corrosion loss is much lower than that of existing single-layer laser cladding coatings and traditional electroplated chromium coatings. At the same time, the coating of the present invention is not only superior to the control group in terms of mass loss and pitting quantity, but also its surface morphology shows more excellent durability, and is particularly suitable for highly corrosive environments, such as marine, chemical and other fields.
[0133] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A wear-resistant and corrosion-resistant remanufacturing process for products based on laser deposition, characterized in that: The following steps are involved: Surface pretreatment: pre-treat the substrate surface of the product to remove the surface oxide layer, oil stains and other impurities to improve the adhesion of the coating; Preparation of laser cladding coating: On the pretreated substrate surface, a first layer of wear-resistant coating is deposited by laser cladding process, wherein the wear-resistant coating is Fe-based or Co-based multi-component alloy powder; Preparation of ion deposition coating: forming a second layer of corrosion-resistant coating on the first layer of coating by ion deposition process, wherein the corrosion-resistant coating is a ceramic material; Surface post-treatment: Heat treatment and surface finishing of the coating to reduce residual stress and ensure the surface smoothness and durability of the coating.
2. According to the laser deposition-based wear-resistant and corrosion-resistant product remanufacturing process method of claim 1, it is characterized in that: The surface pretreatment comprises the following steps: Sand blasting: Use corundum sand or silicon carbide particles to sandblast the substrate surface to increase the surface roughness; Chemical cleaning: Immerse the substrate surface after sandblasting in a dilute sulfuric acid or hydrochloric acid solution for chemical cleaning to remove surface oxides and impurities; Surface Roughening: Depending on the substrate material, mechanical grinding or chemical etching is used to further roughen the surface to enhance the adhesion of the coating.
3. The wear-resistant and corrosion-resistant remanufacturing process of a product based on laser deposition according to claim 1 is characterized in that: The laser cladding coating preparation comprises the following steps: Select Fe-based or Co-based multi-component alloy powder, the particle size range of the alloy powder is 20 to 100 microns; The laser cladding process is adopted, the laser power is set at 2-4kW, and the cladding scanning speed is controlled at 5-10mm / s; The cladding thickness is controlled at 0.5 to 2.0 mm, and multi-layer uniform cladding is achieved through a cross-scanning path to ensure metallurgical bonding between the coating and the substrate.
4. The wear-resistant and corrosion-resistant remanufacturing process of a product based on laser deposition according to claim 3 is characterized in that: Ti, V and W strengthening elements are added to the laser cladding coating material to form carbide, nitride or boride particles to improve the hardness and wear resistance of the coating. The hardness of the coating reaches above HV600.
5. The wear-resistant and corrosion-resistant remanufacturing process of a product based on laser deposition according to claim 1 is characterized in that: The ion deposition coating preparation comprises the following steps: On the first layer of laser cladding coating, a pulsed arc ion source technology is used to deposit silicon nitride (Si3N4), aluminum oxide (Al2O3) or titanium nitride (TiN) ceramic materials; Adjust the deposition current to 50-200A / cm 2 , ensuring the uniformity and density of the deposited layer; The deposition thickness is controlled to be 10 to 100 microns, and the coating thickness is adjusted according to demand to ensure the corrosion resistance of the coating.
6. The wear-resistant and corrosion-resistant remanufacturing process of a product based on laser deposition according to claim 5 is characterized in that: The particle size of the ceramic material powder is controlled to be 1 to 10 microns, and the deposition atmosphere is 10 -4 ~10 -6 Pa vacuum environment, and introduce nitrogen or oxygen as the reaction gas.
7. The wear-resistant and corrosion-resistant remanufacturing process of a product based on laser deposition according to claim 1 is characterized in that: The surface post-treatment comprises the following steps: The coating is subjected to low-temperature annealing treatment at 200-400°C for 2-4 hours to eliminate residual stress inside and outside the coating; Use mechanical polishing or ultra-precision polishing technology to fine-process the coating surface so that the surface roughness reaches the mirror state of Ra0.2~0.4; Cooling curve control, gradually reducing the coating temperature to prevent stress concentration caused by differences in thermal expansion coefficients.
8. The wear-resistant and corrosion-resistant remanufacturing process of a product based on laser deposition according to claim 1 is characterized in that: The multi-layer coating structure is a double-layer or multi-layer composite coating. The first layer is a wear-resistant laser cladding layer, and the second layer is a corrosion-resistant ceramic deposition layer. The layers are metallurgically bonded to achieve stress-free transition.
9. The wear-resistant and corrosion-resistant remanufacturing process of a product based on laser deposition according to claim 8, characterized in that: The thickness and material composition of each layer in the multilayer coating can be adjusted according to different working conditions, specifically including a functional gradient coating that gradually transitions from the inside to the outside, wherein the first layer contains a metal-ceramic composite material and the second layer is a pure ceramic material.
10. The wear-resistant and corrosion-resistant remanufacturing process of a product based on laser deposition according to claim 9, characterized in that: The hardness of the functional gradient coating is designed to gradually increase from the inside to the outside, wherein the hardness of the inner layer is HV600, and the hardness of the outer ceramic coating can reach above HV1000, meeting the requirements of high wear and high corrosion service environments.
Citation Information
Cited By
Composite valve and manufacturing method thereof
CN120231884A
High-temperature-resistant and wear-resistant stainless steel for pneumatic cylinder and preparation method of stainless steel
CN120350377A
Ceramic chopper regeneration process based on supercritical collaborative ALD repair
CN120425315A
A ceramic wedge knife regeneration process based on supercritical synergistic ald repair
CN120425315B